Microbial modeling of thermal resistance of Alicyclobacillus acidoterrestris CRA7152 spores in concentrated orange juice with nisin addition - Peña,Wilmer Edgard Luera (2009)
The nisin effect on thermal death of Alicyclobacillus acidoterrestris CRA 7152 spores in concentrated orange juice (64ºBrix) was studied. Concentrations of 0, 50, 75 and 100 IU of nisin/ml juice, at temperatures of 92, 95, 98 and 102ºC were evaluated. The quadratic polynomial model was used to analyze the effects of the factors and their interaction. Verification of surviving spores was carried out through plating in K medium (pH 3.7). The results showed that the D values without nisin addition were 25.5, 12.9, 6.1 and 2.3 min for 92, 95, 98 and 102ºC respectively. With addition of nisin into the juice there was a drop of heat resistance as the concentration was increased at a same temperature. With 30, 50, 75, 100 and 150 IU/ml at 95ºC, the D values were 12.34, 11.38, 10.49, 9.49 and 9.42 min respectively, showing that a decrease in the D value up to 27% can be obtained. The second order polynomial model established with r² = 0.995 showed that the microorganism resistance was affected by the action of temperature followed by the nisin concentration. Nisin therefore is an alternative for reducing the rigor of the A. acidoterrestris CRA 7152 thermal treatment.